The Role of Patient Experience in Improving the Quality of Hospital Services in DKI Jakarta - Alfira Ulfa; MF. Arrozi Adhikara; Erry Yudhya Mulyani (International Forum of Researchers and Lecturers, 2025)
Hospitals in DKI Jakarta continue to face service quality challenges, including long waiting times, fragmented information systems, and limited patient access to digital health technologies. Although digital transformation and digital literacy are expected to enhance service quality, the mediating role of patient experience remains insufficiently explored. This study investigates the effects of digital transformation and digital literacy on service quality, with patient experience as a mediating variable. A quantitative explanatory design was applied using data from 200 outpatients. Measurements were based on validated indicators of digital transformation, digital literacy, patient experience, and service quality. Structural Equation Modeling (SEM) with AMOS was employed for analysis. The findings show that digital transformation significantly improves patient experience and service quality. Digital literacy positively affects patient experience but does not directly influence service quality. Patient experience fully mediates the relationship between digital literacy and service quality and partially mediates the effect of digital transformation. These results highlight the critical role of patient experience in translating digital capabilities into perceived service improvements. Hospitals are encouraged to strengthen digital transformation initiatives, enhance digital literacy support—especially for older adults—and design user-friendly digital services that facilitate communication and access. This study integrates the Technology Acceptance Model and Customer Experience Theory to provide empirical evidence on how digital-based interventions can advance hospital service quality.